1999
DOI: 10.1007/s003830050644
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing gut in infants with gastroschisis

Abstract: Infants born with gastroschisis (GS) in association with intestinal atresia are well described, however, atresia to the extent where none or very little of the midgut remains has rarely been reported. In this paper we present one infant born with a GS defect in combination with total loss of the midgut and another with a tight GS defect with atresia of the proximal and distal midgut at the regions where the bowel had gone through the abdominal wall. On examining these and other case reports in the literature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
9

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 0 publications
0
14
0
9
Order By: Relevance
“…In the majority of vanishing gastroschisis cases reported in the literature, an external stump of bowel adjacent to the umbilicus is evident at birth even when the underlying defect has closed [9,10,11,12,13,14,15]. In cases 1-3 the external abdominal appearances were entirely normal.…”
Section: Discussionmentioning
confidence: 88%
“…In the majority of vanishing gastroschisis cases reported in the literature, an external stump of bowel adjacent to the umbilicus is evident at birth even when the underlying defect has closed [9,10,11,12,13,14,15]. In cases 1-3 the external abdominal appearances were entirely normal.…”
Section: Discussionmentioning
confidence: 88%
“…A review of the literature shows that these cases are rare, since only 7 cases were found [1,3,[5][6][7][8][9] (table 1). The case presented demonstrates part of the natural history of this unusual complication of gastroschisis.…”
Section: Discussionmentioning
confidence: 99%
“…Kimble et al [3] reviewed 8 cases of reported extensive gut atresia with no childhood survivor. Table 1 shows that none of the previous reported cases of extensive resorption of extraabdominal bowels in fetuses with gastroschisis survived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another theory is that a volvulus occurs, which in turn leads to infarction and reabsorption of small bowel. 4 The baby will be born with either a small (<1 cm) or no abdominal wall defect remaining. The extrinsic bowel is then either reabsorbed or mummified.…”
Section: Introductionmentioning
confidence: 99%